Impacts of silver-coated antimicrobial screen covers on the cell-phone microbiome of resident physicians - McCumber, Alexander W. (Infect Control Hosp Epidemiol, 2019)
An antimicrobial screen was applied to the cell phones of 26 resident physicians to determine its effects on the phone microbiome and its potential to serve as a selective agent for antibiotic or silver resistance genes. No increase of these genes was observed now was there a shift in the overall microbial community.